Testing the Environmental Seismic Intensity scale on data derived from the earthquakes of 1626, 1759, 1819, and 1904 in Fennoscandia, northern Europe - Mäntyniemi, Päivi; Sørensen, Mathilde B.; Tatevossian, Ruben E. (Geosciences, 2021)
Earthquake environmental effects (EEEs) were compiled for the earthquakes of 1626, 1759, 1819, and 1904 in the Fennoscandian Peninsula, northern Europe. The principal source of information was the contemporary newspaper press. Macroseismic questionnaires collected in 1759 and 1904 were also consulted. We prepared maps showing newly discovered EEEs together with previously known EEEs and analyzed their spatial distribution. We assigned intensities based on the 2007 Environmental Seismic Intensity (ESI) scale to 27 selected localities and compared them to intensities assigned based on the 1998 European Macroseismic Scale. While the overall agreement between the scales is good, intensities may remain uncertain due to the sparsity of written documentation. The collected data sets are most probably incomplete but still show that EEEs are not unprecedented cases in the target region. The findings include landslides and rockfalls as well as cascade effects with a risk potential and widespread water movements up to long distances. The winter earthquake of 1759 cracked ice over a large area. This investigation demonstrates that the ESI scale also has practical importance for regions with infrequent EEEs. Peer reviewed